2009
DOI: 10.1021/ac901530g
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition of Two-Dimensional Chiral Supramolecular Nanostructure Tuned by Electrochemical Potential

Abstract: Molecular chiralty and phase transition of p-phenylenedi(rcyanoacrylicacid) di-n-ethyl ester (p-CPAEt) assembled on Au(111) have been studied in the electric double layer region in 0.1 M HClO 4 by electrochemical scanning tunneling microscopy (ECSTM) technique. Three types of chiral supramolecular nanostructures were resolved at differently charged interfaces. Within a potential range (0.65 V < E < 0.8 V, region I), a close-packed physisorbed adlayer of chiral stripe pattern, with the (3 × 6) structure, has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 47 publications
2
7
0
1
Order By: Relevance
“…The rod length was measured to be approximately 1.8 nm, in agreement with the theoretical length of the DSP molecule. The series of bright protrusions in a linear configuration are a contrast feature typical of STM images for a planar-oriented conjugated aromatic molecule physisorbed on a substrate surface [20,21]. A similar STM contrast and stripe pattern was also reported for a DSP derivative adsorbed in a flat configuration on highly orientated pyrolytic graphite [22].…”
Section: Stripe Pattern (055 V→075 V)supporting
confidence: 68%
“…The rod length was measured to be approximately 1.8 nm, in agreement with the theoretical length of the DSP molecule. The series of bright protrusions in a linear configuration are a contrast feature typical of STM images for a planar-oriented conjugated aromatic molecule physisorbed on a substrate surface [20,21]. A similar STM contrast and stripe pattern was also reported for a DSP derivative adsorbed in a flat configuration on highly orientated pyrolytic graphite [22].…”
Section: Stripe Pattern (055 V→075 V)supporting
confidence: 68%
“…This behavior was also observed by UHV-STM [38]. In addition to the order–order transition of achiral rod-like molecules, other 2D chiral structures have also been constructed [39]. …”
Section: Dynamics Of 2d Supramolecular Structuresmentioning
confidence: 60%
“…Moreover, it is known that CPAEt molecules that contain two cyano groups gives three different nanopatterns on Au(111) electrodes with respect to the applied potential region selected. 37 These authors have also shown that these patterns can be reversibly switched through the polarisation. These results are particularly interesting in that the meta-stable -form of entacapone has only previously been prepared under non-equilibrium conditions by anti-solvent drown out or by interphase conversion from another polymorph form .…”
Section: Figure 3 Structural Characterisation Of the Crystal Orientatmentioning
confidence: 95%
“…For example, the charge density at an electrode surface can be fine-tuned by an external electric field which can change the configuration and strength of surface adsorption and even result in the formation of different surface structures. [28][29][30][31][32][33][34][35][36][37] To the authors' knowledge there has been no published research in which low magnitude dc polarisation has been applied to a SAM template with the aim to effect the direction and control of the polymorphic form. Previous studies have, though, demonstrated that strong electric fields can be used to enhanced crystal nucleation, 38,39 promote the preferred orientation of crystals 40 and to direct polymorphs.…”
Section: Introductionmentioning
confidence: 99%